2011
DOI: 10.1007/s10404-011-0930-2
|View full text |Cite
|
Sign up to set email alerts
|

A multilayered microfluidic system with functions for local electrical and thermal measurements

Abstract: Microfluidic systems have been extensively applied in research of chemistry, biology and fluidic dynamics. In these applications, local and precise measurements are often crucial for reliable results. We demonstrate here a multilayered, multifunctional microfluidic platform with embedded electrodes open to the microchannel and thermocouple sensors underneath the microchannel that are suitable for local electrical and thermal measurements, respectively. We demonstrate that precise transport measurements with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The testing results showed that over an area of diameter 40–100 μm, the sensors could detect a weak surface temperature difference of 0.1–0.2 K. The merits of simple structure, stable performance, and compatible process to standard semiconductor techniques make the sub-micron sensors applicable in solid electronic devices, microfluidic systems, and even for bio-sensing at the cell level. For instance, it may detect local temperature distribution on an active electronic device with a better temperature resolution than what has been reported [ 33 ], or replace conventional thin-film thermocouples as the built-in sensor arrays in sophisticated lab-on-a-chip systems [ 34 ], and show better performance as they can also be fabricated with their sensing junctions open to the fluid channel [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The testing results showed that over an area of diameter 40–100 μm, the sensors could detect a weak surface temperature difference of 0.1–0.2 K. The merits of simple structure, stable performance, and compatible process to standard semiconductor techniques make the sub-micron sensors applicable in solid electronic devices, microfluidic systems, and even for bio-sensing at the cell level. For instance, it may detect local temperature distribution on an active electronic device with a better temperature resolution than what has been reported [ 33 ], or replace conventional thin-film thermocouples as the built-in sensor arrays in sophisticated lab-on-a-chip systems [ 34 ], and show better performance as they can also be fabricated with their sensing junctions open to the fluid channel [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, as schematically shown in Fig. 2 b, a Ti/Au film (5/100 nm) was patterned on a 4″ glass wafer by photolithography (Instrument: SUSS, MBJ4), coating process (Instrument: Kurt J. Lesker, PVD 75), and lift-off process to function as the electrodes [ 59 ]. Then, a 300-nm-thick spin-on-glass (SOG) (Futurrex, Inc, China) was spin-coated on the wafer as the dielectric layer.…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of a thermocouple of is one order of magnitude better than for RTDs and the actual voltage measurement is straightforward. Additionally, using cleanroom facilities, it is possible to reduce the size of the junction (measuring point) to 0.1 m [ 105 , 106 , 107 ]. However, the voltage level is rather low, so that external electric fields can induce some noise.…”
Section: Temperature Measurementsmentioning
confidence: 99%